Opossums : an adaptive radiation of New World marsupials - Voss, Robert S.; Jansa, Sharon A. (Johns Hopkins University Press, 2021)
"Voss and Jansa have synthesized what is currently known about the marsupials of the Americas, the opossums, including the coauthors' own research findings on opossum diversity, comparative biology, and natural history. They provide a coherent and original portrait of opossums' adaptive radiation in the New World"--